Enhancing sustainability through the integration of relational contracting elements in BIM contractual framework for the Malaysian construction industry - Mohd Halimi, Fatimah Aqilah; Abdullah Habib, Siti Nora Haryati; Ismail, Syuhaida (Malaysian Institute Of Planners, 2025)
Construction projects involve a myriad of parties with distinct roles that often result in fragmentation, coordination challenges and adversarial relationships. The emergence of Building Information Modelling (BIM) has been regarded as one of the driving forces for integration and collaboration among project stakeholders. Nevertheless, the additional contractual risks brought by BIM may undermine its benefits, as the failure to address these risks could potentially lead to more disputes. Given that construction projects fundamentally rely on contracts to govern stakeholders’ relationships, the present study aims to promote social sustainability in BIM-based construction by incorporating relational contracting elements (RCE) into BIM Protocol context, which in this study refers to a supplementary contractual arrangement used to govern BIM-related roles, responsibilities and risk allocation. Using data gathered from a research survey conducted among industry players in Malaysia and analysed through factor analysis, the study identified sixteen (16) significant BIM contractual risks that need to be addressed, and twenty-five (25) factors grouped under three (3) relational contracting elements (RCEs) that should be considered in BIM-enabled contractual arrangements. The findings are expected to contribute towards embedding sustainability in BIM-based construction projects in Malaysia